2004
DOI: 10.1207/s15324796abm2803_2
|View full text |Cite
|
Sign up to set email alerts
|

Has there been a delay in the age of regular smoking onset among African Americans?

Abstract: Background: It is not clear whether the decline in African 1992-1993, 1995-1996-1999, and reconstructed year of smoking initiation and calculated age-specific incidence of initiation from 1970 to 1992. We then compared detailed age-specific rates of initiation for two 5-year periods selected to be before and after the documented large declines in African American adolescent smoking. Results: In the time period after marked declines in AfricanAmerican adolescent smoking (1987)(1988)(1989)(1990)(1991)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Fourth, we used a tobacco deprivation manipulation in which the participant was not blind to condition; hence, we cannot disentangle the relative effects of sensorimotor loss of the smoking ritual, expectancy effects, or nicotine-mediated pharmacological changes. Fifth, later average age of daily smoking onset may be unique to this sample potentially due to the high proportion of African-Americans who tend to begin smoking later than some other racial/ethnic groups (Trinidad, Gilpin, Lee, & Pierce, 2004), which ultimately may affect the breadth of populations that these findings generalize to. Sixth, we showed that the composite withdrawal symptom index mediated smoking reinstatement effects in this study but did not include validated measures that isolate individual non-affective symptoms (e.g., hunger).…”
Section: Discussionmentioning
confidence: 98%
“…Fourth, we used a tobacco deprivation manipulation in which the participant was not blind to condition; hence, we cannot disentangle the relative effects of sensorimotor loss of the smoking ritual, expectancy effects, or nicotine-mediated pharmacological changes. Fifth, later average age of daily smoking onset may be unique to this sample potentially due to the high proportion of African-Americans who tend to begin smoking later than some other racial/ethnic groups (Trinidad, Gilpin, Lee, & Pierce, 2004), which ultimately may affect the breadth of populations that these findings generalize to. Sixth, we showed that the composite withdrawal symptom index mediated smoking reinstatement effects in this study but did not include validated measures that isolate individual non-affective symptoms (e.g., hunger).…”
Section: Discussionmentioning
confidence: 98%
“…As in lung cancer treatment, disparities also loom in tobacco treatment and are likely a result of multiple predisposing risk factors. blacks initiate smoking later (average age at onset, 17.4 years for blacks versus 14.7 years for whites; p Ͻ .05) [21] and smoke fewer cigarettes per day than whites (14.1 versus 18.4 cigarettes per day) [21,22]. However, despite later initiation, black adults smoke at rates similar to whites (black men, 23.9%; black women, 19.2%; white men, 24.5%; white women, 19.8%) [23].…”
Section: Blacks Are At Risk For Continued Smoking and Poor Cessation mentioning
confidence: 99%
“…Interestingly, populations of Black-African descent are also characterized by unique smoking patterns. Despite having a similar prevalence of current smoking as Caucasians [13], populations of Black-African descent report later ages of smoking initiation [14,15] and lower cigarette consumption [16,17]. Furthermore, populations of Black-African descent suffer from disproportionately higher rates of most tobacco-related illnesses [17], such as lung cancer [18,19], despite their lower levels of smoking.…”
Section: Introductionmentioning
confidence: 99%